Zeolite-cellulose polyacrylamide composite hydrogel and its preparation and application
Through the clinselin and loaded amparim material in the polyacrylamide hydrogel, prepare the amporor-cellulose polyacrylamide composite hydrogel, solve the problem of insufficient intensity and adsorption ability of traditional hydrogels, and achieve efficient removal of removal The heavy metal in the water body and soil realizes the recycling of adsorbents through physical methods.
Patent Information
- Application Number
- CN202211385851.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-11-07
AI Technical Summary
When used in sewage or complex soil environments, traditional polyacrylamide hydrogels have poor strength and adsorption capacity, are difficult to use for a long time, are easily consumed and decomposed, and adsorbents are difficult to recover, which poses a risk of secondary pollution.
The cellulose polyacheramide hydrogel is legally legally polymerized, and the amplastic material is prepared to prepare the amporor-cellulin polyacrylamide composite hydrogel to form a dual network structure to improve the mechanical performance and adsorption ability. The physical method realizes the separation of the adsorption agent and the environmental medium.
The high water absorption, strong adsorption capacity and good mechanical performance of composite hydrogel can effectively remove heavy metals in water bodies and soil, and realize the recovery of adsorptions through physical methods, reducing environmental load.
Smart Images

Figure CN115678043B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental heavy metal treatment, and specifically relates to a zeolite-cellulose polyacrylamide composite hydrogel and a preparation method and application thereof. Background Art
[0002] Heavy metal pollution poses a serious threat to food safety and human health. After entering water and farmland soil, heavy metals are easily accumulated and difficult to degrade. They are also enriched in agricultural products and even in human bodies through the food chain, posing a serious threat to food safety, human health and agricultural production. Therefore, effective treatment of heavy metal pollution is imminent.
[0003] At present, adsorption is an efficient and environmentally friendly remediation technology for heavy metal pollution treatment. However, traditional adsorbents are difficult to recover after being added to water and soil as heavy metal adsorption materials, resulting in the long-term presence of adsorbents in water and soil environments, which poses a risk of secondary pollution. Therefore, separating the adsorbent and the heavy metals it adsorbs from the soil is more sustainable and safer for heavy metal remediation in water and soil.
[0004] Polyacrylamide hydrogel has a three-dimensional network structure and has the characteristics of absorbing water but being insoluble in water. It can be separated from water and soil in a simple way. However, the strength and adsorption capacity of traditional polyacrylamide hydrogel are poor, making it difficult to use as an adsorbent for a long time in sewage or complex soil environments. Problems such as hydrogel matrix loss and decomposition are prone to occur. How to modify and improve the adsorption effect and strength of polyacrylamide has become the focus of this technology. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing a zeolite-cellulose polyacrylamide composite hydrogel. Cellulose is grafted onto polyacrylamide hydrogel and loaded with zeolite material by free radical polymerization to prepare a double-network composite hydrogel material with good mechanical properties, high water absorption and strong adsorption capacity. The adsorbent can be separated from the environmental medium by physically removing the adsorbent, and the effect of repairing heavy metal-contaminated water and soil can be achieved by removing heavy metals.
[0006] Another object of the present invention is to provide a zeolite-cellulose polyacrylamide composite hydrogel prepared by the above method for repairing heavy metal polluted water and soil.
[0007] Another purpose of the present invention is to provide the application of zeolite-cellulose polyacrylamide composite hydrogel in the removal of heavy metals from water or soil. Nano zeolite material as a nano filler can significantly enhance the mechanical strength of cellulose acrylamide hydrogel on the one hand, and as a negatively charged functional carrier, it can effectively improve the adsorption effect of composite hydrogel material on cationic heavy metals; the gel network skeleton is constructed by cellulose and positively charged cationic polyacrylamide, which can effectively adsorb negatively charged heavy metal ions in water or soil; at the same time, as a three-dimensional porous hydrophilic material, the hydrogel exhibits strong water absorption and swelling properties in the water environment, and can simultaneously adsorb positively and negatively charged heavy metal ions free in the environment during the water absorption and swelling process. The strong mechanical properties make the gel remain intact after the adsorption is completed, and the gel can be removed from the water or soil by physical methods, and finally achieve the purpose of effectively realizing the removal and repair of heavy metals in heavy metal-contaminated water or soil.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel comprises the following steps:
[0010] (1) taking a zeolite material, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, maleic anhydride, and a crosslinking agent, adding water and stirring to dissolve, thereby obtaining a mixed solution 1;
[0011] (2) adjusting the pH value of the mixed solution 1 to 4-5, adding cellulose and stirring until swelled, to obtain a mixed solution 2; adjusting the pH value of the mixed solution 2 to 7-8, adding an initiator and a coupling agent tetramethylethylenediamine, stirring thoroughly, placing the mixed solution in a mold, letting it stand, demolding, and drying, to obtain a zeolite-cellulose polyacrylamide composite hydrogel;
[0012] The zeolite in step (1) is Na-X zeolite or clinoptilolite, preferably sieved through a 100-mesh sieve;
[0013] The cross-linking agent in step (1) is N,N'-methylenebisacrylamide and / or hexamethylenebisacrylamide, preferably N,N'-methylenebisacrylamide;
[0014] The zeolite material, acrylamide and acryloyloxyethyl trimethyl ammonium chloride in step (1) are preferably in a mass ratio of (1.71-3.22):16.50:(1.83-5.50);
[0015] The cellulose in step (2) is sodium carboxymethyl cellulose and / or calcium carboxymethyl cellulose, preferably sodium carboxymethyl cellulose, with a viscosity of 3000 to 5000 mpa, USP grade;
[0016] The mass ratio of cellulose to acrylamide in step (2) is 1.00:(7.50-8.75), preferably 1.00:8.25;
[0017] The initiator in step (2) is potassium persulfate or ammonium persulfate;
[0018] The order of adding the initiator and the coupling agent in step (2) is: first add the initiator and stir until it is completely dissolved, then add the coupling agent;
[0019] The mass volume ratio of the initiator to the coupling agent in step (2) is 0.75 g: (250-300 μL), preferably 0.75 g: 250 μL.
[0020] The zeolite-cellulose polyacrylamide composite hydrogel prepared by the above method can be used to remove heavy metals, especially heavy metals in water or soil;
[0021] Specifically, the hydrogel is placed in a water body contaminated by heavy metals (or the soil contaminated by heavy metals is first dispersed in water), adsorbed for at least 24 hours, and then the hydrogel is removed by a physical method to obtain treated water and soil;
[0022] The adsorption treatment time is preferably 1-5 days;
[0023] The physical method is preferably filtering or sieving.
[0024] Compared with the prior art, the present invention has the following advantages and effects:
[0025] 1. The zeolite-cellulose polyacrylamide composite hydrogel of the present invention organically combines acrylamide and cellulose through chemical covalent bonds, so that the composite hydrogel has stronger chemical bonds and intermolecular forces. The presence of zeolite also promotes the formation of the porous structure of the composite hydrogel. These two points significantly improve the environmental strength and structural stability of the composite hydrogel, facilitate use and recycling, and reduce the environmental load.
[0026] 2. The zeolite-cellulose polyacrylamide composite hydrogel of the present invention has an excellent effect on removing heavy metals. After adsorbing pollutants, it can be separated from the environment through simple operations, thereby achieving the effect of removing heavy metals from the polluted environment.
[0027] 3. The zeolite-cellulose polyacrylamide composite hydrogel of the present invention has a wide range of applications, can be applied to heavy metal-contaminated water and soil, and has good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The water absorption bar graph of the hydrogels prepared in Examples 1 to 3 and Comparative Example 1.
[0029] Figure 2 It is a bar graph showing the adsorption effect of Examples 1, 3 and Comparative Example 1 on cationic heavy metal Cd(II).
[0030] Figure 3 It is a bar graph showing the adsorption effect of Examples 1 and 4 on anionic heavy metal As(III).
[0031] Figure 4 The bar graph is a graph showing the effective Cd content in the soil heavy metal removal experiment of Examples 2 to 3, Comparative Example 2 and a blank control group (without adsorbent), wherein the Cd-contaminated soil conditions are the same.
[0032] Figure 5 This is a bar graph showing the recovery rate of the hydrogel after the soil heavy metal removal experiment in Examples 2 to 3 and Comparative Example 2.
[0033] Figure 6 It is the strain-stress curve diagram of Examples 1 to 3 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0035] Example 1
[0036] A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel comprises the following steps:
[0037] (1) 3.22 g of sieved (100 mesh sieve, the same below) Na-X type zeolite material, 16.50 g of acrylamide, 5.5 g of acryloyloxyethyl trimethylammonium chloride, 6.65 g of maleic anhydride, and 0.1 g of N,N'-methylenebisacrylamide were added to 100 ml of deionized water and magnetically stirred to dissolve completely to obtain a mixed solution 1;
[0038] (2) dropping 5 mol / L sodium hydroxide solution into the mixed solution 1 obtained in step (1) to adjust the pH to 4-5, adding 2 g of cellulose and stirring magnetically for 0.5 h, and then dropping 3 mol / L sodium hydroxide solution to adjust the pH to 7-8 to obtain a mixed solution 2;
[0039] (3) Add 0.75 g of potassium persulfate as an initiator to the mixed solution 2 obtained in step (2), and then add 250 μL of a coupling agent, tetramethylethylenediamine. After sufficient stirring, put the mixture into a mold and let it stand for 0.5 h to obtain a composite hydrogel material for removing heavy metals.
[0040] The composite hydrogel sample was placed in a 100-mesh nylon filter bag and immersed in excess pure water for 24 hours at room temperature. The surface moisture was then wiped off with filter paper and weighed. The calculated water absorption is shown in Figure 1.
[0041] The water absorption rate is calculated according to equation 1-1: W t and W d are the weight of the hydrogel swollen to time t and the weight of the dried hydrogel, respectively.
[0042]
[0043] Example 2
[0044] A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel comprises the following steps:
[0045] (1) 3.22 g of sieved clinoptilolite material, 16.50 g of acrylamide, 5.50 g of acryloyloxyethyl trimethylammonium chloride, 6.65 g of maleic anhydride, and 0.1 g of N,N'-methylenebisacrylamide were added into 100 ml of ultrapure water and magnetically stirred to dissolve completely to obtain a mixed solution 1;
[0046] (2) dropping 5 mol / L sodium hydroxide solution into the mixed solution 1 obtained in step (1) to adjust the pH to 4-5, adding 2 g of cellulose and stirring magnetically for 0.5 h, and then dropping 3 mol / L sodium hydroxide solution to adjust the pH to 7-8 to obtain a mixed solution 2;
[0047] (3) Add 0.75 g of potassium persulfate as an initiator to the mixed solution 2 obtained in step (2), and then add 250 μL of a coupling agent, tetramethylethylenediamine. After sufficient stirring, put the mixture into a mold and let it stand for 0.5 h to obtain a composite hydrogel material for removing heavy metals.
[0048] The water absorption rate of the obtained composite hydrogel sample is as follows: Figure 1 .
[0049] Example 3
[0050] A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel comprises the following steps:
[0051] (1) 1.71 g of sieved Na-X zeolite material, 16.50 g of acrylamide, 5.5 g of acryloyloxyethyl trimethylammonium chloride, 6.65 g of maleic anhydride, and 0.15 g of N,N'-methylenebisacrylamide were added to 100 ml of deionized water and magnetically stirred to dissolve completely to obtain a mixed solution 1;
[0052] (2) dropping 5 mol / L sodium hydroxide solution into the mixed solution 1 obtained in step (1) to adjust the pH to 4-5, adding 2 g of sodium carboxymethyl cellulose and stirring magnetically for 0.5 h, and then dropping 3 mol / L sodium hydroxide solution to adjust the pH to 7-8 to obtain a mixed solution 2;
[0053] (3) Add 0.75 g of potassium persulfate as an initiator to the mixed solution 2 obtained in step (2), and then add 250 μL of a coupling agent, tetramethylethylenediamine. After sufficient stirring, put the mixture into a mold and let it stand for 0.5 h to obtain a composite hydrogel material for removing heavy metals.
[0054] The water absorption rate of the obtained composite hydrogel sample is as follows: Figure 1 .
[0055] Example 4
[0056] A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel comprises the following steps:
[0057] (1) 3.22 g of sieved Na-X zeolite material, 16.50 g of acrylamide, 4.13 g of acryloyloxyethyl trimethylammonium chloride, 6.65 g of maleic anhydride, and 0.1 g of N,N'-methylenebisacrylamide were added into 100 mL of ultrapure water and magnetically stirred to dissolve completely to obtain a mixed solution 1;
[0058] (2) dropping 5 mol / L sodium hydroxide solution into the mixed solution 1 obtained in step (1) to adjust the pH to 4-5, adding 2 g of cellulose and stirring magnetically for 0.5 h, and then dropping 3 mol / L sodium hydroxide solution to adjust the pH to 7-8 to obtain a mixed solution 2;
[0059] (3) Add 0.75 g of potassium persulfate as an initiator to the mixed solution 2 obtained in step (2), and then add 250 μL of a coupling agent, tetramethylethylenediamine. After sufficient stirring, put the mixture into a mold and let it stand for 1 hour to obtain a composite hydrogel material for removing heavy metals.
[0060] In order to demonstrate the unique advantages of the composite hydrogel material of the present invention, a cellulose polyacrylamide hydrogel without zeolite loading was prepared by comparative example 1, and a blank hydrogel without zeolite loading and grafted cellulose was prepared by comparative example 2:
[0061] Comparative Example 1
[0062] A hydrogel, which is different from Example 1 in that no zeolite is added during the preparation process.
[0063] The water absorption rate of the obtained hydrogel sample is Figure 1 .
[0064] The water absorption rate of the hydrogel is directly related to its affinity for water. The hydrogel prepared in Comparative Example 1 contains a large number of hydrophilic groups: -COO-, -COOH, -CONH2, -O-. These hydrophilic groups enable the hydrogel prepared in Comparative Example to have better water absorption and swelling capabilities.
[0065] like Figure 1 As shown in the figure, the water absorption rate of the composite gel after loading zeolite is lower than that of the control hydrogel without zeolite. This is because the synergistic effect between the hydrogel matrix and zeolite is relatively weak. A large amount of zeolite doped and loaded in the hydrogel will affect the network structure of the hydrogel and weaken the possible synergistic molecular effect between the aqueous solution and the hydrogel network, thereby reducing the water absorption rate of the composite gel. However, the composite hydrogel with added zeolite can still absorb hundreds of times more water than its own weight and has high water absorption performance.
[0066] Comparative Example 2
[0067] A hydrogel, which is different from Example 1 in that zeolite and grafted cellulose are not added during the preparation process.
[0068] Example 5
[0069] 0.09 g of the hydrogel prepared in Examples 1, 3 and Comparative Example 1 was added to 30 mL of 64.15 mg·L -1 Cd(Ⅱ) solution at 180 r·min -1 , (25±2)℃ for 24h, filter out the hydrogel, and measure the concentration of cadmium ions in the solution before and after treatment by atomic absorption spectrophotometry (AAS) after dilution. The experimental results are as follows Figure 2 .
[0070] Depend on Figure 2 It can be seen that the adsorption effect of the hydrogels in Examples 1 and 3 on cadmium ions is significantly greater than that in Comparative Example 1, and the addition of zeolite helps to enhance the removal rate of cadmium by the hydrogel, and by comparing Example 1 with Example 3, it can be seen that the increase in the zeolite loading ratio will further enhance the adsorption effect of the composite gel on cadmium. It can be seen that the present invention uses zeolite to modify the cellulose polyacrylamide hydrogel, which significantly enhances its adsorption effect on heavy metals.
[0071] Example 6
[0072] 0.09 g of the composite hydrogel prepared in Examples 1 and 4 was added to 30 mL of 1.51 mg·L -1 As(Ⅲ) solution at 180r·min -1 , (25±2)℃ for 24h, filter out the hydrogel, and dilute and measure the As(Ⅲ) concentration in the solution before and after treatment by atomic fluorescence spectrometry. The experimental results are as follows Figure 3 .
[0073] The As(III) removal rate of the hydrogel in Example 4 is 70.25%, which is slightly lower than the As(III) removal rate of 74.85% in Example 1. This is because as the cationic monomer acryloyloxyethyltrimethylammonium chloride (DAC) increases, the cationic degree of the composite gel also increases, thereby enhancing the adsorption effect of the composite gel on arsenic in the solution system.
[0074] Example 7
[0075] Weigh 20g of soil contaminated with cadmium (Cd), add deionized water to flood the soil to 2cm (simulate the flooding of rice fields), add 5 grains (0.5g) of hydrogel prepared in Examples 2, 3 and Comparative Example 2, respectively, and incubate at 25°C for 5 days, sieve out the hydrogel, separate the water layer from the soil layer, air-dry, grind, and pass through a 100-mesh sieve. -1 Diethylenetriaminepentaacetic acid (DTPA) solution was used to extract the available cadmium in the soil. The experimental results are as follows Figure 4 After the soil heavy metal adsorption experiment, the composite hydrogel can be removed and recovered by filtering or fishing out with a sieve.
[0076] After soil treatment, the number of composite hydrogels collected was counted and recorded as n1. The hydrogel recovery rate can be calculated by equation 1-2. The experimental results are shown in Figure 5 .
[0077]
[0078] After adsorption and separation of the composite hydrogel materials of Examples 2 and 3, the recovery rate was 100%, and the effective cadmium content in the soil decreased significantly. However, the comparative example did not contain zeolite as an active adsorption site for heavy metals, and had a poor adsorption effect on the effective cadmium in the soil.
[0079] Example 8
[0080] The composite gels prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 were molded into cylindrical shapes and subjected to compression tests using a UTM-4204 electronic universal tester manufactured by Shenzhen Sansi Zongheng. The compression strength (85% deformation) of each example is shown in Table 1, and the corresponding strain-stress curves are shown in Figure 6 shown.
[0081] Figure 6 The compressive strength of the cellulose polyacrylamide hydrogel prepared in Comparative Example 1 is greater than that of the blank gel prepared in Comparative Example 2. After cellulose is grafted with acrylamide, chemical covalent bonds organically combine acrylamide and cellulose, making the hydrogel have stronger chemical bonds and intermolecular forces.
[0082] The compressive strength of the composite hydrogels of Examples 1, 2, and 3 is greater than that of the hydrogels without zeolite material prepared in Comparative Examples 1 and 2. This is because the presence of zeolite also promotes the formation of the porous structure of the composite hydrogel, which significantly improves the compressive strength of the composite hydrogel.
[0083] Table 1 Compression strength
[0084]
[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a zeolite-cellulose polyacrylamide composite hydrogel, characterized in that The following steps are involved: (1) taking a zeolite material, acrylamide, acryloyloxyethyl trimethyl ammonium chloride, maleic anhydride, and a crosslinking agent, adding water and stirring to dissolve, thereby obtaining a mixed solution 1; (2) adjusting the pH value of the mixed solution 1 to 4-5, adding cellulose and stirring until swelled, to obtain a mixed solution 2; adjusting the pH value of the mixed solution 2 to 7-8, adding an initiator and a coupling agent tetramethylethylenediamine, stirring thoroughly, placing the mixed solution in a mold, letting it stand, demolding, and drying, to obtain a zeolite-cellulose polyacrylamide composite hydrogel; The mass ratio of the zeolite material, acrylamide and acryloyloxyethyl trimethyl ammonium chloride in step (1) is (1.71-3.22):16.50:(1.83-5.50); The mass ratio of cellulose to acrylamide in step (2) is 1.00:(7.50-8.75).
2. The preparation method according to claim 1, characterized in that: The zeolite in step (1) is Na-X zeolite or clinoptilolite; The cross-linking agent in step (1) is N,N'-methylenebisacrylamide and / or hexamethylenebisacrylamide.
3. The preparation method according to claim 1, characterized in that: The cellulose described in step (2) is sodium carboxymethyl cellulose and / or calcium carboxymethyl cellulose.
4. The preparation method according to claim 1, characterized in that: The cellulose described in step (2) is sodium carboxymethyl cellulose with a viscosity of 3000-5000 MPa.
5. A zeolite-cellulose polyacrylamide composite hydrogel, characterized in that The method is prepared by the method described in any one of claims 1 to 4.
6. Use of the zeolite-cellulose polyacrylamide composite hydrogel according to claim 5 in removing heavy metals.
7. Use of the zeolite-cellulose polyacrylamide composite hydrogel according to claim 5 in removing heavy metals from water or soil.
8. The use according to claim 7, characterized in that The following steps are involved: The hydrogel is placed in a water body contaminated by heavy metals and subjected to adsorption treatment for at least 24 hours, and then the hydrogel is removed by a physical method to obtain a treated water body.
Citation Information
Patent Citations
Method for preparing nanometer composite gel for removing bivalent cadmium in wastewater
CN107915803A
Hydrogel as well as preparation method and application thereof
CN112175152A
Preparation and application of cellulose nanocrystal reinforced composite gel for heavy metal ion adsorption
CN115228443A